Occupational Mobility in Farming Sector: An Analysis in Coastal and Tribal Districts of Odisha, India - Jena, Anshuman; Kanungo, Aditya Prasad (Indian Journal of Extension Education, 2022)
The continuous migration of Indian rural youth from farming to the non-farming sector has caused concern among the policy makers. If not checked, it is likely to affect the future agricultural activities and thereby future agrarian economy. Present research was carried out during 2020 with a comparative analysis among the respondents of the coastal district (Jagatsinghpur) and tribal district (Mayurbhanj) of Odisha with a randomly chosen sample of 480 respondents, 240 from each district including 120 each from the first-generation (father) and second-generation (son). The study aimed to find out prevalence of intergenerational occupational mobility in farming sector by using transition probability matrix to describe the pattern of mobility and direction of their movement. A statistically significant difference was found between occupations of the first and second generation in both tribal and coastal districts with hhigher occupational mobility in the coastal district. The coastal district showed a 19.17 per cent decrease in the numbers of farmers than the tribal district. The result showed 49 per cent and 62 per cent of absolute mobility rates in intergenerational occupation in tribal and coastal districts, respectively. There was prevalence of both upward and downward mobility in occupation in the farming sector in both tribal and coastal districts of Odisha.
Keywords: Coastal; Farming; Mobility; Intergenerational; Occupation; Tribal